PENGARUH KEMITRAAN TERHADAP PRODUKSI DAN PENDAPATAN USAHATANI SAYURAN DI KABUPATEN BOGOR - Susanti Susanti; Nunung Kusnadi; Dwi Rachmina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2014)
The partnership between Gapoktan Rukun Tani and vegetable farmers in Bogor was designed to facilitate farmers in overcoming the limitations of production inputs, capital, and market certainty. This study compares a one year production and income of vegetables farmers who participate in the partnership to the non participated vegetables farmers in Bogor. Income analysis and R/C ratio analysis show that the partnership has no influence in increasing the farm production and income. In term of average production, income and R/C ratio, the partnership farmer was lower than that of non partnership farmer (0,96%, 0,97%, and 1,03 lower consecutively). However, the partnership farming increases the bargaining power of farmers by getting higher price and market certainty. Another advantage of paticipating in the partnership is higher access to both capital credit and production input.